Initiating Global Civil Society as a Strategy for Handling the COVID-19 Public Health Threat: A Policy Review - Ayuningtyas, Dumilah; Ul Haq, Hayyan; Utami, Raden Roro Mega (UI Scholars Hub, 2020)
The spread of coronavirus disease 2019 (COVID-19) has had a serious impact on public health. The speed and extent of its spread have demonstrated a global failure to cultivate awareness and cooperation in response to the threat. Therefore, in order to improve public awareness and the management of public health threats, we propose a strategy to initiate global civil society. Using Walt and Gilson's policy triangle framework for policy analysis, we reviewed and analysed a series of articles and policies related to COVID-19, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the Global Health Security Agenda (GHSA), health resilience in the context of globalization, as well as other countries’ experiences. The study also explored constitutional obligations, public health legislation, collaboration of civil society, and policies related to public health, as well as their implementation. Every country has its own public policy strategy for handling COVID-19. One possible solution is to expand the GHSA commitments and bind all countries that have signed the agreement to a single public policy strategy for the handling of COVID-19. The poor handling of the COVID-19 outbreak has demonstrated the need for Indonesia’s civil so- ciety collaboratively oversee the Indonesia’s government’s implementation of its constitutional obligations. The government must make public health security a top priority, and collectives of educated individuals with a strong, shared vision must harness the power of non-governmental advocacy.